Competitive Cooperation between Territories in the Modern Economic Space - Vazhenina, Irina Svyatoslavovna; Vazhenin, Sergey Grigoryevich (Economy of Regions, 2020)
The article examines the economic nature and scope of competitive cooperation between territories, which is becoming an increasingly important economic phenomenon. We hypothesise that competition and cooperation between territories are not mutually exclusive, but complementary. This fact leads to the emergence and development of competitive cooperation. Additionally, we define the factors that, on the one hand, boost the development of competitive cooperation, and, on the other hand, hinder its formation. The paper identifies a number of features characterising the evolution of competitive cooperation between territories: cooperation is specifically time-limited; any cooperation has inherent risk; its formation and implementation always involve certain financial, intellectual, labour and other costs. We emphasise that the existence of relevant projects is an essential prerequisite for the establishment of territorial cooperation. Furthermore, the examination of the positive experience of territories that have already successfully implemented joint projects plays an important role in the formation and development of competitive cooperation. In this context, the active use of benchmarking techniques can be of significant help. We pay a particular attention to the fact that cooperation is always accompanied by certain self-limitations of territories, meaning that partner territories have to sacrifice something in order to reach consensus. The results of the expert surveys allowed us to clarify potential results of competitive cooperation in the Russian Federation. We assessed the willingness of territories (regions, municipalities) to cooperate. What is more, we formulated the proposals on the selection of the most promising forms and directions of competitive cooperation between territories, focusing on the establishment and maintenance of confidence in the economy, which is the basis of cooperation. The research results can be used for designing and implementing the strategies of the socio-economic development of regions and municipalities in the modern economic space.